2012
DOI: 10.1521/ijct.2012.5.3.240
|View full text |Cite
|
Sign up to set email alerts
|

Brooding Rumination and Internalizing Symptoms in Childhood: Investigating Symptom Specificity in a Multi-Wave Prospective Study

Abstract: Specificity of brooding rumination as a cognitive vulnerability for anxiety and depression was examined using the tripartite theory as a framework. The three factors of the tripartite theory (negative affect, positive affect, and physiological hyperarousal) were included in the same structural equation model (latent growth curves) to test three competing hypotheses: brooding rumination as a depression-specific vulnerability (i.e., brooding uniquely predicts shared negative affect + specific positive affect), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Although originally conceptualized as a specific risk factor for depression, there is evidence emerging of relations between rumination and anxiety in children and adolescents (e.g., Lopez, Felton, Driscoll, & Kistner, 2012; Muris, Fokke, & Kwik, 2009). Rumination has been identified as a potential transdiagnostic factor for depression and anxiety in early adolescents (McLaughlin & Nolen-Hoeksema, 2011), and has been shown to account for the relations between these two conditions (McLaughlin & Nolen-Hoeksema, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally conceptualized as a specific risk factor for depression, there is evidence emerging of relations between rumination and anxiety in children and adolescents (e.g., Lopez, Felton, Driscoll, & Kistner, 2012; Muris, Fokke, & Kwik, 2009). Rumination has been identified as a potential transdiagnostic factor for depression and anxiety in early adolescents (McLaughlin & Nolen-Hoeksema, 2011), and has been shown to account for the relations between these two conditions (McLaughlin & Nolen-Hoeksema, 2011).…”
mentioning
confidence: 99%
“…In support of this theory, rumination is associated with a past history of major depressive episodes, predicts future depressive symptoms and depressive episodes, and predicts a greater duration of future episodes of depression in children and early adolescents (e.g., Abela & Hankin, 2011, Abela, Hankin, Sheshko, Fishman, & Stolow, 2012; Abela, Vanderbilt, & Rochon, 2004). Although originally conceptualized as a specific risk factor for depression, there is evidence emerging of relations between rumination and anxiety in children and adolescents (e.g., Lopez, Felton, Driscoll, & Kistner, 2012; Muris, Fokke, & Kwik, 2009). Rumination has been identified as a potential transdiagnostic factor for depression and anxiety in early adolescents (McLaughlin & Nolen-Hoeksema, 2011), and has been shown to account for the relations between these two conditions (McLaughlin & Nolen-Hoeksema, 2011).…”
mentioning
confidence: 99%
“…En cuanto a las dimensiones de la rumiación cognitiva, la rumiación reproche presentó una mayor explicación de la variable latente en el modelo; se logró explicar un 82 % de la varianza de la depresión y un 75 % en ansiedad, hallazgos que coinciden con los modelos de especificidad de síntomas según el modelo tripartito de los problemas emocionales y los hallazgos en estudios similares previos (López et al, 2012). Al parecer, la combinación entre rumiación cognitiva y los síntomas emocionales (efectos directos) estarían asociados a la experiencia de respuestas de malestar (efectos indirectos del NA) con un papel mediador parcial (efectos indirectos), tal como indicaron reportes previos sobre vulnerabilidad cognitiva a partir de contenidos esquemáticos negativos y estrés cotidiano (Ciesla, Felton & Roberts, 2011), y el procesamiento rumiativo pre-evento y post-evento en la ansiedad social (Modini, Rapee & Abbott, 2018), que indicaría el papel causal y sus variaciones en la respuesta emocional dada la intensidad del NA.…”
Section: Discussionunclassified
“…Brooding rumination, first described by Nolen-Hoeksema and Morrow (1991), involves a passive comparison of one's current situation to ideal and desired standards. This type of rumination is strongly associated with negative affect and has been described as a cognitive vulnerability (Lopez et al, 2012). Studies have also found that brooding rumination is associated with ED pathology in both clinical and non-clinical samples (Naumann et al, 2015;Seidel, et al, 2016;Startup, et al, 2013;Gordon, et al, 2012;Holm-Denoma & Hankin, 2010).…”
Section: Emotional Regulationmentioning
confidence: 95%